Synthesis of Chitosan Nanoparticles via Microfluidic Approach: The Role of Temperature in Tailoring Aggregation for Enhanced Uniformity - Muqarrab Ahmed; Yangcheng Lu (Micromachines, 2025)
This study presents the synthesis of chitosan nanoparticles (CSNPs) using a microfluidic device. Microfluidic rapid mixing enables fast nucleation for small-sized nuclei, but a high PDI value like 0.956 shows uncontrollable growth of small nuclei, resulting in the formation of larger and more variable aggregates at room temperature. High temperatures play a key role in controlling the growth of CSNPs to enhance uniformity. Temperatures of 40 °C and 50 °C promote controlled interactions among small nuclei, while increasing the temperature to 80 °C further accelerated the curing process, suitable for synthesizing CSNPs with various sizes. At 80 °C, size regulation can be achieved by changing the TPP concentration, which controls surface curing and affects the size as well. These results emphasize the impact of elevated temperature and precise TPP concentration for product quality control and modulation in CSNPs’ synthesis.